2001
DOI: 10.1074/jbc.m103544200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Brain-specific Box C/D Small Nucleolar RNA Processed from Tandemly Repeated Introns of a Noncoding RNA Gene in Rats

Abstract: Antisense box C/D small nucleolar RNAs (snoRNAs) guide the 2-O-ribose methylations of eukaryotic rRNAs and small nuclear RNAs (snRNAs) through formation of a specific base pairing at each RNA methylation site. By analysis of a box C/D snoRNA cDNA library constructed from rat brain RNAs, we have identified a novel box C/D snoRNA, RBII-36, which is devoid of complementarity to rRNA or an snRNA and exhibits a brain-specific expression pattern. It is uniformly expressed in all major areas of adult rat brain (excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 66 publications
1
50
1
1
Order By: Relevance
“…4B). In fact, a similar enrichment of ncRNA expression in brain versus other tissues has previously been demonstrated in mouse (Ravasi et al 2006), and several reports on the involvement and relative abundance of ncRNA in human CNS function and development have recently emerged (Cavaille et al 2001;French et al 2001;Pollard et al 2006;Sone et al 2007). Furthermore, an RNAz screen of porcine EST sequences revealed that developmental brain tissue seems to contain more ncRNAs than other tissues (Seemann et al 2007).…”
Section: Experimental Verificationmentioning
confidence: 75%
“…4B). In fact, a similar enrichment of ncRNA expression in brain versus other tissues has previously been demonstrated in mouse (Ravasi et al 2006), and several reports on the involvement and relative abundance of ncRNA in human CNS function and development have recently emerged (Cavaille et al 2001;French et al 2001;Pollard et al 2006;Sone et al 2007). Furthermore, an RNAz screen of porcine EST sequences revealed that developmental brain tissue seems to contain more ncRNAs than other tissues (Seemann et al 2007).…”
Section: Experimental Verificationmentioning
confidence: 75%
“…Moreover, it would be expected that increasing numbers of genes would have evolved solely to express RNA as higher-order regulators in this increasingly complex system. This will have occurred at least in part by gene duplication followed by loss of protein-coding capacity, as appears to have happened in Xist (the ncRNA controlling X chromosome inactivation in female mammals) (Duret et al, 2006) and in many of the non-protein-coding genes that encode snoRNAs or miRNAs in their introns (Cavaille et al, 2001;Mattick and Makunin, 2005;Rodriguez et al, 2004;Tycowski et al, 1996;Ying and Lin, 2005). Interestingly, many ncRNAs are alternatively spliced (Cocquet et al, 2005;Pang et al, 2005), suggesting that there is an operational distinction between RNA sourced from exons and introns.…”
Section: Digital-analogue Conversion Of Rna Signalsmentioning
confidence: 99%
“…A subset of box H/ACA snoRNAs is located in Cajal bodies (a class of small nuclear organelle), and are sometimes called scaRNAs (small Cajal body RNAs) (Meier, 2005), where they modify telomerase RNA in a cell-cycle dependent manner (Jady et al, 2004;Jady et al, 2003). At least some snoRNAs exhibit tissue-specific and developmental regulation and/or imprinting (Cavaille et al, 2000;Cavaille et al, 2002;Cavaille et al, 2001;Rogelj and Giese, 2004), which is indicative of a regulatory function. There are also a number of so-called 'orphan' snoRNAs without known targets (Cavaille et al, 2000;Cavaille et al, 2002;Cavaille et al, 2001;Huttenhofer et al, 2001;Kiss et al, 2004;Vitali et al, 2003), one of which has recently been shown to be involved in the aberrant splicing of the serotonin receptor 5-HT(2C)R gene in Prader-Willi syndrome patients (Cavaille et al, 2000;Kishore and Stamm, 2006).…”
Section: Rna Modification and Rna Editingmentioning
confidence: 99%
“…The Snurf-Snrpn domain therefore shares common genomic and epigenetic features with the Dlk1-Dio3 domain (Cavaille et al, 2002;Cavaille et al, 2001;Royo et al, 2007;Royo and Cavaille, 2008) (Fig. 1).…”
Section: Snord115-hg and Snord116-hg Transcripts Are Nuclearretained mentioning
confidence: 99%